Accuracy in measurement of elevation gain in road cycling - Menaspà, P.; Haakonssen, E.; Sharma, A.; Clark, B. (Journal of Science and Cycling, 2016)
Purpose. Accurate measures of elevation gain are important for monitoring energy expenditure and physical load. The aim of this study was to determine the accuracy of barometric devices used for measuring elevation gain.